A novel peptide inhibitor of Dll4‐Notch1 signalling and its pro‐angiogenic functions. (11th January 2022) - Zhu, Guofu; Lin, Ying; Ge, Tandi; Singh, Shekhar; Liu, Hao; Fan, Linlin; Wang, Shumin; Rhen, Jordan; Jiang, Dongyang; Lyu, Yuyan; Yin, Yiheng; Li, Xiankai; et al.
Abstract : Background and Purpose: The Dll4‐Notch1 signalling pathway plays an important role in sprouting angiogenesis, vascular remodelling and arterial or venous specificity. Genetic or pharmacological inhibition of Dll4‐Notch1 signalling leads to excessive sprouting angiogenesis. However, transcriptional inhibitors of Dll4‐Notch1 signalling have not been described. Experimental Approach: We designed a new peptide targeting Notch signalling, referred to as TAT‐ANK, and assessed its effects on angiogenesis. In vitro, tube formation and fibrin gel bead assay were carried out, using human umbilical vein endothelial cells (HUVECs). In vivo, Matrigel plug angiogenesis assay, a developmental retinal model and tumour models in mice were used. The mechanisms underlying TAT‐ANK activity were investigated by immunochemistry, western blotting, immunoprecipitation, RT‐qPCR and luciferase reporter assays. Key Results: The amino acid residues 179–191 in the G‐protein‐coupled receptor‐kinase‐interacting protein‐1 (GIT1‐ankyrin domain) are crucial for GIT1 binding to the Notch transcription repressor, RBP‐J. We designed the peptide TAT‐ANK, based on residues 179–191 in GIT1. TAT‐ANK significantly inhibited Dll4 expression and Notch 1 activation in HUVECs by competing with activated Notch1 to bind to RBP‐J. The analyses of biological functions showed that TAT‐ANK promoted angiogenesis in vitro and in vivo by inhibiting Dll4‐Notch1 signalling. Conclusions and Implications: We synthesized and investigated the biological actions of TAT‐ANK peptide, a new inhibitor of Notch signalling. This peptide will be of significant interest to research on Dll4‐Notch1 signalling and to clinicians carrying out clinical trials using Notch signalling inhibitors. Furthermore, our findings will have important conceptual and therapeutic implications for angiogenesis‐related diseases.